Engineering low clinker Strain-Hardening cementitious composites (SHCC) using polyethylene and cost-effective polypropylene fibers: An experimental scale-linking analysis - Ameer Hamza Ahmed; Julia Hübner; Dominik Junger; Cesare Signorini; Marko Butler; Marco Liebscher; Christina Scheffler; Viktor Mechtcherine (Materials & Design)
This paper reports on an experimental scale-linking study aimed at the design and mechanical characterization of low-clinker and cost-efficient strain-hardening cementitious composites (SHCC). Three distinct matrices were examined, each comprising a limestone calcined clay cement (LC3) binder with reduced Portland cement (PC) contents of 50 %, 35 %, and 25 %. These fine-grained matrices were reinforced with cost-effective and low-tenacity polypropylene (PP) fibers, while high-performance and expensive polyethylene (PE) fibers were used as a benchmark. Various micro-, meso-, and macro-scale mechanical and analytical tests were performed after 28 days of curing age, including single fiber pull-out, uniaxial tensile testing on notched and unnotched specimens, flexure, compression testing, digital image correlation analysis, and environmental scanning electron microscopy. The results clearly showed that the low tensile strength and high compliance of PP, when combined with a low-strength matrix containing only 25 wt% PC, contributed to better strain-hardening behavior, attributed to the fine-tuning of the micromechanical design of the interacting phases. Naturally, such a design significantly enhances the sustainability credentials of SHCC while at the same time increasing its cost-saving potential, evening out the response of high-performance and costly PE fibers incorporated into a high-strength matrix (e.g., with 50 wt% PC).